Aphrodisiac Potentials of Aqueous Extract of Azanza Garckeana Fruit Pulp in Fluoxetine-induced Sexually-impaired Female Rats - Nurudeen, Quadri Olaide; Asinmi, Muhammed Robiu; Falana, Mansurat Bolanle; Dikwa, Muhammad Ali (Journal of Science and Technology, 2023)
This study aims to investigate the potential of Azanza garckeana, a plant traditionally used as an aphrodisiac, to reverse sexual dysfunction induced by an antidepressant ‘fluoxetine’ in female rats. Aqueous extract of A. garckeana fruit pulp was screened for its secondary metabolite compositions. Female rats were induced into sexual dysfunction using fluoxetine, then they were divided into six groups, and treated based on the group with oral administration of varying doses of A. garckeana extract (125, 250, and 500 mg/kg body weight) and a reference medication (Tadalafil) for seven days. Sexual behaviour parameters were monitored and hormone levels (progesterone, follicle-stimulating hormone, luteinizing hormone, oestrogen, and prolactin) were measured after the treatment period. Fluoxetine significantly (p < 0.05) reduced the frequencies of sexual behaviours in the rats, such as darting, hopping, lordosis, genital grooming, and licking behaviour, but increased the latencies of darting and hopping. However, the extract, at 250 and 500 mg/kg, significantly (p < 0.05) reversed these changes in the sexual behavior of fluoxetine-induced rats in comparison to the effects of Tadalafil treatment. Furthermore, the extract significantly (p < 0.05) increased the levels of luteinizing hormone, follicle-stimulating hormone, progesterone, and prolactin in the blood but decreased oestrogen levels, especially at a dose of 500 mg/kg. The results of this study suggest that the aqueous extract of A. garckeana fruit pulp can improve sexual behavior and reproductive hormone concentrations, thereby potentially restoring sexual competence in sexually-dysfunctioned female rats. These findings provide additional support for the traditional use of A. garckeana in managing female sexual dysfunction.